The psychobiology of child and parental stress and the subjective perception of parental stress in a clinical sample of children - Melinder, Annika; Brænden, Astrid; Lebena, Andrea; Olsen Faresjö, Åshild; Theodorsson, Elvar; Coldevin, Marit; Stubberud, Jan; Zeiner, Pål (Frontiers in Child and Adolescent Psychiatry, 2023)
Parental stress may influence the assimilation of treatment strategies and affect a child´s recovery trajectory. Thus, assessing parental stress is crucial for children requiring psychiatric care. The Parenting Stress Index (PSI) is widely utilized to gauge perceived parental stress. However, since the PSI does not quantify cortisol concentration (i.e., a biological marker for stress), it’s vital to ascertain the alignment between these indicators. Moreover, understanding the correlation in cortisol concentrations between parents and children in clinical contexts can refine assessment and diagnostic methodologies. In an outpatient sample (Mage = 9.68 years), we examined the correlation between parent and child hair cortisol concentration (HCC) in 60 pairs, analyzed the relationship between PSI scores and parent HCC (n = 65), and used a regression model to probe the influence of child HCC and PSI scores on parent HCC (n = 63). Results showed a significant relationship between parent and child HCC (p < .001). The ‘Distraction and Hyperactivity’ PSI subscale correlated significantly with parent HCC (p = .02). None of the PSI scores correlated with child HCC (p´s > .07). The regression model, accounting for 44% of the variance, demonstrated that only child HCC significantly predicted parent HCC (p < .001), while the ‘Distraction and Hyperactivity’ subscale, did not.